„Krąg” i jego krąg. Wydawnictwo w świetle relacji - Łaszczyński, Marcin (Pamięć i Sprawiedliwość, 2010)
This study describes a history of one of the most significant clandestine publishing houses in Poland, during 1980–1989. The article based on accounts of witnesses and archive records of the Institute of National Remembrance, is an attempt to make readers familiar with not only the history of the “Krąg” Publisher, but also with realities of functioning of the samizdat (illegally self-published and self-distributed literature) editions. Furthermore, the text concentrates on some important issues such as: technical facilities, sophisticated methods of acquiring printing materials and on the process of publishing books. According to the author, it is also worth stressing the fact of invaluable assistance of foreign countries, such as: the so-called “drops” (special transports with technical help) and a helpfulness in obtaining copyrights on particular publications. What is more, the article tries to trace the way of the “Krąg” Publisher being watched by the Security Service, which in consequence weakened its position on the independent publishing market.